2009
DOI: 10.1038/leu.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from multiple myeloma patients display distinct genomic profile as compared with those from normal donors

Abstract: It is an open question whether in multiple myeloma (MM) bone marrow stromal cells contain genomic alterations, which may contribute to the pathogenesis of the disease. We conducted an array-based comparative genomic hybridization (array-CGH) analysis to compare the extent of unbalanced genomic alterations in mesenchymal stem cells from 21 myeloma patients (MM-MSCs) and 12 normal donors (ND-MSCs) after in vitro culture expansion. Whereas ND-MSCs were devoid of genomic imbalances, several non-recurrent chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
108
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 55 publications
2
108
0
2
Order By: Relevance
“…Several previous studies indicated that BM-derived MSCs from MM patients showed an enhanced production of cytokines and a distinctive gene expression profile, as compared with their normal counterparts. [1][2][3][4] Although osteoblastic function is decreased in advanced MM, regarding whether and at which level the differentiation of MSCs towards osteoblasts is impaired in this disease, the reports are not unanimous. [1][2][3] In the present study, MSCs from both normal subjects (healthy human donors or naive mice) and MM subjects (MM patients or 5T33MM mice) were used.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies indicated that BM-derived MSCs from MM patients showed an enhanced production of cytokines and a distinctive gene expression profile, as compared with their normal counterparts. [1][2][3][4] Although osteoblastic function is decreased in advanced MM, regarding whether and at which level the differentiation of MSCs towards osteoblasts is impaired in this disease, the reports are not unanimous. [1][2][3] In the present study, MSCs from both normal subjects (healthy human donors or naive mice) and MM subjects (MM patients or 5T33MM mice) were used.…”
mentioning
confidence: 99%
“…Our data do not allow to conclude whether the impaired osteogenic differentiation of MM-hMSCs is due to an inherent difference, although the genomic profile in ND-hMSCs and MMhMSCs was reported to be much different. 4 We assume that with the persistent stimulation of MM cells in vivo, hMSCs gradually gain abnormalities in gene expression and/or certain signaling pathways of osteoblast differentiation, such as Notch signaling. These abnormalities of MM-hMSCs might still exist in vitro even though MM cells are removed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has been previously reported that MSCs are cytogenetically normal by FISH analysis, supporting the notion that MM cells and MSCs have no common progenitor. 4 Clearly, our study data should be confirmed in a larger set of patient-derived samples. At present, there are no published studies of isolated OBs in MM patients.…”
mentioning
confidence: 99%
“…Alterations of gene expression and genomic profiles have been reported in MSCs of MM patients in comparison with healthy donors as published in Leukemia. 3,4 Moreover, we have recently shown the occurrence of different patterns of gene expression profile, not only in MSCs but also in OBs of MM patients compared with healthy individuals and in relationship to MM bone disease. 5 Nevertheless, it is still unclear whether these bone microenvironment cells in MM patients are primarily tumoral.…”
mentioning
confidence: 99%